Translation and the Dialectics of Difference and Equivalence: Some Theoretical Propositions for a Redefinition of the Source-Target Text Relation - Tack, Lieven (Meta, 2000)
AbstractAt which level of analysis (descriptivist, empirical, epistemological), and along which perspective (sociological, linguistical, communicative), should we locate the distinctive criteria for the definition of translation? In other words, what are the necessary and sufficient conditions which constitute the object « translation,» exclusively this object and not any other object? This is the general question of this article. It will be developped in two steps. First, we shall try to demonstrate that the perspective adopted by translatology, in defining translation by its semantical and fonctional equivalence relation with a source text, is congenetically determined by the discursive exclusion of the theorisation of that which is the very condition of possibility of each translation: the disrupture and distancing by which humans structure their social relation. Consequently, it is by the critique of communication theory, where a large part of translatology has drawn its scientific foundations, that we can deliver sound arguments for the assessing of translation in the structure of social relations. A second step consists in the formulation of a working hypothesis: if translation may be caused by the social dialectics of distancing and negociation of meaning, it is not sufficiently specified by this logic. It could be hypothesized that translation finds its specificity in the hybridity of the linguistic referential relation it instaures with the mute universe to be conceptualized on the one hand, and with the source text to be reformulated on the other.